Exploring Maxim Flouting in “A Man Called Otto” Movie: A Pragmatic Study - Wulantari, Ni Putu Adelia; Maharani, Putu Devi (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2023)
The term flouting maxim refers to a situation in which a speaker deliberately fails to uphold one of Grice’s conversational maxims, called the Grice a maxim: quantity, quality, relation, and manner. In the movie A Man Called Otto, there were several times when the cast committed violations of the maxim. Due to the discovery of these problems, the primary aims of this study are to ascertain the various categories of maxims that are flouted within the movie “A Man Called Otto,” and to provide an explanation of the situational context underlying the character’s dialogues that involve the flouting of maxims. The data were analyzed by the theory proposed by Cutting, (2002) as the leading theory to find out the types of flouting maxims, and the theory context of the situation offered by Halliday, M. A. K., & Hasan, (1989) was used. In this study, the method utilized for analyzing the data was a descriptive qualitative, while observing and note-taking techniques were used in collecting the data. The results of this study indicate that the characters in the movie “A Man Called Otto” flouted the conversational maxims. The maxim of relation was found to be the most frequently flouted, followed by the maxim of quantity, the maxim of quality, and lastly, the maxim of manner.